2017
DOI: 10.3390/en10091385
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Impact Assessment of Groundwater Heat Pumps (GWHPs): Rigorous vs. Simplified Models

Abstract: Groundwater Heat Pumps (GWHPs) are increasingly adopted for air conditioning in urban areas, thus reducing CO 2 emissions, and this growth needs to be managed to ensure the sustainability of the thermal alteration of aquifers. However, few studies have addressed the propagation of thermal plumes from open-loop geothermal systems from a long-term perspective. We provide a comprehensive sensitivity analysis, performed with numerical finite-element simulations, to assess how the size of the thermally affected zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 50 publications
2
24
0
1
Order By: Relevance
“…Such systems have stringent requirements related to the medium for removing indoor heat. Piga et al, Sedaghat et al, Todorov et al, and Al-Madhlom et al studied the use of TES for different areas [9][10][11][12][13]. Song et al used an indoor sandbox test to simulate different operation modes of pumping and recharging well and found the results were well [14].…”
Section: Introductionmentioning
confidence: 99%
“…Such systems have stringent requirements related to the medium for removing indoor heat. Piga et al, Sedaghat et al, Todorov et al, and Al-Madhlom et al studied the use of TES for different areas [9][10][11][12][13]. Song et al used an indoor sandbox test to simulate different operation modes of pumping and recharging well and found the results were well [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on GSHP systems [24,25] have shown that final COP depends on system configuration and local site conditions (e.g., the BHEs setup, the climate, the ground properties, and the HP nominal power), as well as the transient operative conditions of the system's duty-cycle: the ground's undisturbed temperature, the temperature difference between the surface and the underground, and the temperature of the water leaving the heat pump and the BHEs. These temperature fluctuations lower the system COP.…”
Section: Introductionmentioning
confidence: 99%
“…Urban heat islands and global warming trends also impact groundwater temperatures, as highlighted by recent studies such as [14,15]. Shallow geothermal installations upstream of the P&T may impact the groundwater temperature, propagating the so-called thermal plumes through advection, dispersion and, to a lesser extent, conduction [16,17]. A further possible alteration is represented by thermal recycling, which occurs when part of the reinjected water returns to the abstraction well [18,19].…”
Section: Technical Solutions For the Geothermal Exploitation Of Pandt Smentioning
confidence: 99%
“…While the geothermal exploitation of P&T systems is still at an early stage, the mining sector offers several examples of pumped groundwater thermal use, especially for building and district heating systems, which reduces the overall environmental costs of such operations. Farr et al (2016) [8] reported that, so far, 16 GWHP systems have been installed in flooded mines in Europe and USA, with the first applications dating back to the early 1980s. System capacities range between 18 and 700 kW, and depths range between 65 and 600 m below ground level.…”
Section: Introductionmentioning
confidence: 99%